Spelling Bee Games to Increase Students' Vocabulary Mastery at the Islamic-Affiliated Middle Schools: An Action Research - Rahmawati, Wiki Tedi; Harahap, Yunita Mutiara (JOLLT Journal of Languages and Language Teaching, 2023)
Spelling bee game can be considered as a method to teach vocabulary mastery for junior high school using a game. The students not only memorize the words abut also can spell and pronounce them correctly. There are problems faced by the students particularly the seventh grade students of this research location such as the difficulty to understand the form of English words and to pronounce them. The objective of this research was to solve those problems in order to increase the students' mastery of vocabulary by applying spelling bee game. The research method used was a classroom action research by fulfilling planning, acting, observing, and reflecting in each cycle. It was accomplished in two cycles since the determined achievement was not obtained in the first cycle. The subject involved was 35 students of grade seventh. Qualitative data were gathered by administering interview, observation, and questionnaire while quantitative data were obtained from students' vocabulary mean score. The qualitative data analysis from questionnaire showed that there was increasing of positive responses (23.97%) while observation and interview showed that the students were more motivated in engaging the teaching-learning process through spelling bee game. The quantitative data analysis showed that there was increasing on students' vocabulary mastery seen from the increasing of mean score from 25.07% in orientation test to 88.57% in post-test cycle II. There were 31 students in post-test cycle II passed the criteria. Thus, the criteria of success were achieved. It can be concluded that using spelling bee game can be an alternative method to increase the vocabulary mastery in an enjoyable and fun atmosphere.